2023
DOI: 10.1183/23120541.00643-2022
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled formoterol impairs aerobic exercise capacity in endurance-trained individuals: a randomised controlled trial

Abstract: The 2022 asthma guidelines emphasise inhaled long-acting beta2-agonist formoterol as part of first treatment step, and therefore formoterol use among athletes will likely increase. However, prolonged supratherapeutic use of inhaled beta2-agonist impairs training outcomes in moderately-trained men. Here, we investigated whether inhaled formoterol, at therapeutic doses, imposes detrimental effects in endurance-trained individuals of both sexes.Fifty-one endurance-trained participants (31/20 male/female; maximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 40 publications
0
10
3
Order By: Relevance
“…Another notable effect was that the salbutamol-treated participants temporarily had a lower increase in V ′ O 2max than placebo-treated participants during the first 4 weeks of the training intervention after which the salbutamol-treated participants approximated the change in V ′ O 2max observed in the placebo-treated participants at week 6. Although it could be expected that mitochondrial content would also be compromised, as has been shown for prolonged treatment with formoterol [ 28 ], our data did not support such an effect. In fact, salbutamol seemed to increase mitochondrial content as determined by electron transport complex protein expression, where there was an overall increase with salbutamol treatment.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Another notable effect was that the salbutamol-treated participants temporarily had a lower increase in V ′ O 2max than placebo-treated participants during the first 4 weeks of the training intervention after which the salbutamol-treated participants approximated the change in V ′ O 2max observed in the placebo-treated participants at week 6. Although it could be expected that mitochondrial content would also be compromised, as has been shown for prolonged treatment with formoterol [ 28 ], our data did not support such an effect. In fact, salbutamol seemed to increase mitochondrial content as determined by electron transport complex protein expression, where there was an overall increase with salbutamol treatment.…”
Section: Discussioncontrasting
confidence: 69%
“…[ 27 ] did observe a greater effect of β 2 -agonist on protein synthesis in females than males. And although we, and others, have previously found β 2 -agonists to induce leanness in males [ 15 , 28 , 33 , 36 38 ], concomitant endurance training was shown to blunt this effect [ 23 , 33 ]. This collectively suggests that β 2 -agonists exert sex-specific effects on body composition and that such effects depend on habitual training patterns.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, a recent study demonstrated that formoterol at 48 μg/day for 6 weeks increased muscle mass by 0.7 kg in highly trained males and females, 110 which confirms that formoterol is a potent anabolic beta 2 ‐agonist, as also shown in rodents 111 . However, in line with findings for inhaled terbutaline, 72 daily formoterol inhalation can impair aerobic exercise capacity 110 . In the aforementioned study, trained males and females experienced a 5% decline in VO 2max during formoterol treatment 110 .…”
Section: Performance‐enhancing Effects Of Inhaled Beta2‐agonistsmentioning
confidence: 98%
“…While some of the commonly used drugs in the management of asthma and EIB are permitted, special rules apply to beta 2 -agonists and glucocorticoids to protect athletes' health and prevent misuse for performanceenhancing purposes. Use of beta 2 -agonists at high inhaled doses or via systemic routes can induce muscle hypertrophy and leanness, 62,63,[83][84][85][86][87][88][89] as well as enhance muscle strength and sprint performance. 84,88,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105] For example, oral dosing with salbutamol (16 mg/day) led to greater gains in cross-sectional area of fast-twitch muscle fibers and was associated with better sprint performance than placebo in trained young males undergoing 11 weeks of resistance training.…”
Section: Anti-doping Regulations For Drugs Used In Asthma and Eibmentioning
confidence: 99%